An outline for systematic reform of the investment law regime - Wenhua Shan (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
A multilateral framework on investment could provide an opportunity for a systematic review and reform of the international investment regime. This Perspective considers what features a new regime should incorporate to ensure it is a self-balanced system that evenly serves the interests of host countries and foreign investors.
Keywords: 330